ダイ43ジ ナンキョク チイキ カンソクタイ ナイリク コウドウ ホウコク 2002-2003 (ダイニキ ドームフジ ヒョウショウ シンソウ クッサク ケイカク カンレン) - 齊藤, 隆志; サイトウ, タカシ; 木下, 淳; キノシタ, ジュン; Saito, Takashi; Kinoshita, Jun (2005)
P(論文) 第二期ドームふじ氷床深層掘削計画に関連して,第43次南極地域観測隊越冬隊が実施した内陸における行動を報告する.同計画の初年度として,物資,燃料の輸送を目的とした冬明け中継拠点旅行と,建設・設備作業を中心としたドーム本旅行を実施した.ドーム本旅行では,ドームふじ観測拠点において,同拠点の再開,新掘削場の建設,同拠点での越冬を可能とするための諸作業を実施し,第44次隊ドームふじ観測拠点越冬隊に引き継いだ.これらの内陸旅行のために昭和基地周辺で実施した諸準備についても報告する. Inland activities of wintering party of the 43rd Japanese Antarctic Research Expedition (JARE-43) related to the deep ice coring project at Dome Fuji, Antarctica, II were reported. Two large inland traverses were carried out to transport all needed materials to construct the new drilling site and reopen the Dome Fuji Station for the overwintering of JARE-44. The new drilling site was constructed successfully and the Dome Fuji Station prepared for the wintering party of JARE-44. Preparations for inland traverses made around Syowa Station are also described. departmental bulletin paper